Lessons learnt from the variation across 6741 family/general practices in England in the use of treatments for hypogonadism. (7th March 2021) - Heald, Adrian H.; Stedman, Michael; Whyte, Martin; Livingston, Mark; Albanese, Marco; Ramachandran, Sud; Hackett, Geoff
Abstract: Introduction: We have previously reported rates of diagnosis of male hypogonadism in United Kingdom (UK) general practices. We aimed to identify factors associated with testosterone prescribing in UK general practice. Methods: We determined for 6741 general practices in England, the level of testosterone prescribing in men and the relation between volume of testosterone prescribing and (1) demographic characteristics of the practice, (2) % patients with specific comorbidities and (3) national GP patient survey results. Results: The largest volume (by prescribing volume) agents were injectable preparations at a total cost in the 12‐month period 2018/19 of £8, 172, 519 with gel preparations in second place: total cost £4, 795, 057. Transdermal patches, once the only alternative to testosterone injections or implants, were little prescribed: total cost £222, 022. The analysis accounted for 0.27 of the variance in testosterone prescribing between general practices. Thus, most of this variance was not accounted for by the analysis. There was a strong univariant relation ( r  = .95, P  < .001) between PDE5‐I prescribing and testosterone prescribing. Other multivariant factors independently linked with more testosterone prescribing were as follows: HIGHER proportion of men with type 2 diabetes(T2DM) on target control (HbA1c ≤ 58 mmol/mol) and HIGHER overall practice rating on the National Patient Survey for good experience, while non‐white ethnicity and socio‐economic deprivation were associated with less testosterone prescribing. There were a number of comorbidity factors associated with less prescribing of testosterone (such as T2DM, hypertension and stroke/TIA). Conclusion: Our analysis has indicated that variation between general practices in testosterone prescribing in a well developed health economy is only related to small degree ( r 2  = 0.27) to factors that we can define. This suggests that variation in amount of testosterone prescribed is largely related to general practitioner choice/other factors not studied and may be amenable to measures to increase knowledge/awareness of male hypogonadism, with implications for men's health.